Genome‐wide DNA methylation signatures of tau and amyloid neuropathology: Genetics: Genetics of cognitive aging, other dementia, and endophenotypes. (7th December 2020) - Castanho, Isabel; Murray, Tracey K.; Leung, Szi Kay; Hannon, Eilis; Jeffries, Aaron; Lunnon, Katie; Ahmed, Zeshan; Mill, Jonathan
Abstract: Background: The onset and progression of Alzheimer's disease (AD) is characterized by increasing intracellular aggregation of hyperphosphorylated tau protein and the accumulation of β‐amyloid (Aβ) in the neocortex. Despite recent success in identifying genetic risk factors for AD, the regulatory genomic mechanisms involved in disease progression are not fully understood. DNA methylation (DNAm) is the most widely studied epigenetic modification in human disease, with recent work by our group robustly linking methylomic variation to AD and other neurodegenerative disorders. To date, no study has systematically profiled DNAm in mouse models of AD. This study aimed to relate progressive changes in DNAm to AD neuropathology in the cortex, using transgenic models of amyloid and tau pathology. Method: We used transgenic mice harboring human microtubule‐associated protein tau ( MAPT, rTg4510) and amyloid precursor protein ( APP, J20) mutations to investigate epigenomic and transcriptional changes associated with the development of tau and amyloid pathology. Using sequencing‐based approaches, we quantified changes in DNAm and gene expression identifying genomic signatures paralleling the progression of tau and amyloid across multiple brain regions. Methylomic and transcriptomic changes associated with amyloid and tau pathology were compared to similar data generated from human AD brain. Result: We identified progressive changes in gene regulation associated with the development of AD neuropathology, including changes in DNA methylation and gene expression at loci previously identified in previous and ongoing human AD studies ( Ank1, Hoxa, Abca7, Bin1 ). Of note, significantly upregulated genes were strikingly enriched for genes involved in immune regulation, and significantly downregulated genes were enriched for synaptic function pathways related to AD. This study represents the most systematic analysis of progressive changes in gene expression and DNA modifications in mouse models of AD pathology and the first to focus specifically on the entorhinal cortex, a key region affected early in human AD. Conclusion: Our data provide further evidence for an immune‐response to the accumulation of tau and Aβ, and reveal novel genomic pathways associated with the progression of AD neuropathology.